(untitled) (Journal of Parents and Teachers, 2025)
The article explains that with the new educational law (LOGSE), the subject of Religion takes a backseat, as no exams will be conducted. For this reason, a call is made to religious educators to start considering students’ values and attitudes. Additionally, seven examples are provided for implementing a possible evaluation of religious attitudes.